Multifractal Analysis on Fractal-fractional Repellors - Priyanka, T.M.C.; Gowrisankar, A.; Sathiyaraj, T.; Cao, Yang (Journal of Environmental Accounting and Management, 2026)
This paper introduces fractal-fractional repellors which mirror their corresponding fractal-fractional attractors of chaotic systems. Repellors are interesting if there exists special attractors when time is reversed. The phase diagrams of fractal-fractional derivative of rotationally invariant system are presented to discuss its dynamic evolution when a plane of equilibria is introduced. The degree of complexity and chaotic nature of fractal-fractional repellors are observed using time histories upon modifying both fractal and fractional orders. In addition, results are obtained to assure that the repellors underlying the fractal-fractional system possess multifractal structure which in turn reveals the non-uniform distribution of points.